Investigation of nickel oxide and germanium for Li-ion battery anodes - Rahmat, Agung Susantyoko (2015)
We aimed to develop high performance anodes for Li-ion batteries. Three approaches were investigated to minimize the aggregation, pulverization and delamination problems. Firstly, graphitic and amorphous carbon was incorporated to directly-grown NiO nanostructures. NiO-C showed better electrochemical performances than pristine-NiO due to high electrical conductance and better mechanical flexibility of graphitic and/or amorphous carbon. Secondly, vertically-aligned MWCNT arrays were used as base structures for sputtered-NiO, amorphous-Ge and polycrystalline-Ge. The electrochemical performances of MWCNT/NiO were significantly improved than pristine-NiO since vertically-aligned MWCNTs enhanced the ionic and electronic transports and absorbed the stresses during lithiation/delithiation. MWCNT/a-Ge showed higher specific capacity than MWCNT/c-Ge as MWCNT/a-Ge skipped electrochemically-driven solid-state amorphization during first lithiation. MWCNT/a-Ge benefited from low cost processing and low anodic scan peak. Thirdly, annealing treatment was investigated. Annealed-Ge had significantly improved electrochemical performances than as-deposited Ge due to better SS/Ge-film adhesion due to inter-diffusion at SS/Ge interface.